Comparative Pharmacognostical Evaluation and HPTLC Analysis of Stem Bark of Kanchnar (Bauhinia Variegata Linn.) and Kovidar (Bauhinia Purpurea Linn.) (AYUSHDHARA, 2023)
The current study was carried out to provide comparative macroscopy, microscopy, physicochemical parameters and HPTLC analysis of stem bark of Kanchnar (Bauhinia variegata L.) and Kovidar (Bauhinia purpurea L.) T.S. of stem bark of Bauhinia variegata L. shows a wide stratified cork have thin-walled yellow brown cells followed by brown colored cells; inner cork layer has transversely elongated orange brown cells. T.S. of Bauhinia purpurea L of shows presence of few layers of cork, Outer layers contains reddish brown content and inner layers are colourless. Its cortex is composed of 10 to 12 layers of parenchyma cell. Total Ash value found in sample of Kanchnar was 5.67% and in Kovidar was 15.2%. The Alcohol soluble extractive value of Kanchnar was found 29.8 % and of Kovidar was found 4.8%. Water soluble extractive value in sample of Kanchnar was found 20.68% and in Kovidar it was found 13.83%. Reference marker betasitosterol and lupeol was applied on a pre-coated silica gel GF254 plate of uniform thickness (0.2mm). The mobile phase consisting Toluene: Ethyl acetate: formic acid (9:1:0.1). Presence of marker betasitosterol and lupeol in sample of Bauhinia variegata L. were 85.19µg/ml and146.4µg/ml respectively. Presence of marker betasitosterol and lupeol in sample of Bauhinia purpurea L. were 244.6µg/ml and 305µg/ml respectively.